1.8 V, 25.9 nW, 91.86 dB dynamic range second‐order lowpass filter tunable in the range 4–100 Hz. Issue 7 (24th October 2019) - Machha Krishna Reddy, Jayaram Reddy; Laxminidhi, Tonse
Abstract : A second‐order lowpass Butterworth filter with tunable bandwidth capable of offering a dynamic range of 91.86 dB operating on a supply voltage of 1.8 V is presented. The proposed filter is based on a sub‐threshold source follower. The transistor bias currents are switched to enable the bandwidth tuning in the range 4–100 Hz. A proportional to absolute temperature (PTAT) current reference circuit helps to keep the bandwidth intact across process, voltage and temperature variations. The filter, designed in 0.18 µm standard CMOS process, consumes 25.9 nW making it a potential candidate for portable biomedical applications.